Meningkatkan Kesadaran ASI Eksklusif Melalui Edukasi dan Emo Demo di Desa Sucopangepok, Kabupaten Jember, Jawa Timur - Jannah, Miftahul; Ratri, Putri Rahayu; Ayu, Dessya Putri; Kartika, Ria Chandra (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Exclusive breastfeeding coverage in Sucopangepok Village, Jember Regency, has not met the Minimum Service Standard target, partly due to misconceptions about breastfeeding. This community service program aimed to raise awareness of the importance of exclusive breastfeeding among mothers of under-five children. The activity involved 15 participants and was carried out through lectures and emotional demonstrations (emo demo) of breastfeeding and infant stomach capacity using games and hands-on practice. Evaluation was conducted using pretest–posttest, observation, and discussion. Results showed significant improvements in knowledge, with average scores increasing from 64.2% to 84.7% and the proportion of good knowledge rising from 26.7% to 80%. Proper breastfeeding skills improved from 60% to 93.3%, while 93.3% of participants could explain infant stomach capacity using props. Most participants also reported the program as beneficial. In conclusion, this activity effectively promoted exclusive breastfeeding and may support efforts to prevent child malnutrition.